Pengaruh Pelatihan dan Motivasi Kerja Terhadap Produktifitas Karyawan PT Sigzacindo Nusantara - Jepri msai keliat; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study was to determine whether the effect of training and motivation on the productivity of PT Sigzacindo Nusantara (coloni) employees. the method in this research is quantitative. Based on this research, the researcher used quantitative data and distributed questionnaires. The sample in this study used a saturated sample and used validity tests, reliability tests, multiple linear tests and t tests, f tests and the coefficient of determination with the help of SPSS version 22. The t count regression value was 6.360 t count > t table = 6,360 > 1,683. the t- count value is 2.915 where the t-count value > ttable 2.915 > 1.683 it can be said that there is a significant influence of training and motivation on productivity. Based on the results of the calculated F test > F table = 103.787 > 3.23 with a significance value of 0.00 < 0.05, it can be said that training and motivation together have an effect on productivity